Properties of macrophages from high- and low-responder strains of mice. II. The expression of Fc receptors - Vĕtvicka, V; Fornůsek, L; Plocová, D (Folia biologica, 1990)
Simultaneous expression of Fc receptors was studied on the model of peritoneal macrophages from two inbred strains of mice, A/J and C57BL/10ScSn, so-called high- and low-responders. Sheep red blood cells and/or synthetic polymer microspheres both coated with monoclonal antibodies of different isotypes were used for detection of Fc receptors. It was proved that the majority of macrophages bear more than one type of Fc receptors, moreover, macrophages expressing at least three types of Fc receptors simultaneously were detected. Both mouse strains vary in the presence of different subpopulations of macrophages bearing particular sets of Fc receptors.
Keywords: Antibodies, Monoclonal; myši; mužské pohlaví; Male; Erythrocytes; Female; inbrední kmeny myší; Receptors, Fc; kur domácí; receptory Fc; Immunoglobulin G; ženské pohlaví; Chickens; ovce; Lipopolysaccharides; druhová specificita; imunoglobulinové izotypy; Immunization; Immunoglobulin Isotypes; Species Specificity; monoklonální protilátky; Mice, Inbred Strains; Animals; imunizace; lipopolysacharidy; zvířata; Mice; imunoglobulin G; Macrophages; Sheep; peritoneální dutina; makrofágy; Peritoneal Cavity; erytrocyty